The employability skills among students of Public Higher Education Institution in Malaysia - Mohamad Zuber Abd Majid; Muhammad Hussin; Muhammad Helmi Norman; Saraswathy Kasavan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Entering the fourth industrial revolution, many crucial changes took place in the developing economies, especially in the context of the job market. Higher education institution plays an important role in generating labours resources outputs in order to fulfil the demand of the potentials labour in the job market. Hence, strategy in the success of the workforce at the institution of education needs to improve the employability skills. The purpose of this study was to examine the graduates' employability skills among students of Public Higher Education Institution (IPTA) in Malaysia based on demography (gender, location and parental education). In addition, this study also attempts to examine the influencing factors such as endurance force, time management, research experience and activities involvement at university against employability skills. The sample of the study involved 554 undergraduate students in IPTA. The findings show that result on location demographics found significant differences; location was found to affect the level of employability of respondents. The finding also revealed that the factors of endurance force , time management, research experience and activities involvement in university are influencing variances and total predictor factors (75.6%) for employability skills among students IPTA. The contribution of this study can provide a comprehensive comparison of the employability skills based on location demographic and endurance force aspect among the undergraduate in IPTA.